Congenital thyroid teratoma in a newborn: Case report from Ethiopia - Workye Tigabie; Seblewengel Asemie; Fisseha Temesgen (Elsevier, 2020)
Introduction: Teratoma is a germ cell tumor composed of elements from one or more of the three embryonic germ layers. The most common sites of occurrence in childhood are the sacrococcygeal region, gonads, mediastinum, and pineal region and rarely head and neck.[1-6] Cervical teratoma is a rare congenital disease that constitutes about 1-6% of all pediatric teratoma.[3,5] Few of these cervical tumors are very rarely located entirely in the thyroid gland which are called thyroid teratomas.[3,5-8] Case presentation: 17 days old female neonate born to a 32 years old Para III mother presented with right lateral neck swelling and respiratory distress since birth. The neonate underwent surgical excision at age of 20 days through a right transverse cervical incision and the intraoperative finding was a lobulated well defined capsulated cervical tumor measuring 4 * 4 cm with a cystic and solid component. The right lobe of the thyroid gland was not localized, but the left lobe of the thyroid gland was present laterally. Since the tumor has raised from the right lobe of the thyroid gland than from the soft tissue of the neck the tumor is defined as thyroid teratoma instead of cervical teratoma. Besides, the histopathology report confirmed this diagnosis which showed tissue composed of cystic and solid components consisting of the thyroid gland, brain tissue, and skin with the appendages with no immature tissues seen. Conclusion: thyroid teratoma is extremely rare and about 41 cases have been reported in the English literature so far.[5] It is usually benign; however, if not treated properly they can lead to death because of large growth and local effect on vital structures like airway compression.